Anti-acne Emulgel Formulation of Torbangun Leaf Essential Oil (Plectranthus amboinicus (Lour.) Spreng. and Antibacterial Test against Staphylococcus aureus and Propionibacterium acne bacteria - ., Hilmarni; Harsep Rosi, Devahimer; Mulyani, Dwi; Ranova, Riki; Yulia, Mega; Alawiyah, Tuti; Putri, Indah Eka (Asian Journal of Pharmaceutical Research and Development, 2024)
Plectranthus amboinicus (Lour.) Spreng. It is a member of the Lamiaceae family that grows naturally throughout the tropics. This plant contains essential oils that have antimicrobial activity including inhibition against Staphylococcus aureus bacteria. Acne is an inflammation of the skin that can be caused by bacteria such as Staphylococcus aureus, Staphylococcus epidermidis and Propionibacterium acne. For treatment, emulgel preparations are in great demand because they can be used as a better topical drug delivery system. The purpose of this study was to formulate torbangun essential oil emulgel and to determine its antibacterial activity against Staphylococcus aureus and Propionibacterium acne bacteria. Emulgel evaluation includes organoleptic testing, pH, viscosity, spreadability and stability. The results showed that Torbangun essential oil anti-acne emulgel concentrations of 4 and 8% gave strong antibacterial activity against Staphylococcus aureus and Propionibacterium acne bacteria. The emulgel formula that meets the stability test is an anti-acne emulgel formula with a carbomer base.